Anne Bogart: Despre aici și acum - Ardelean, Ioan (Theatrical Research, 2024)
Anne Bogart: About the Here and Now The book A Director Prepares by Anne Bogart offers an engaging look at the world of theater, combining valuable insights and practical ideas for directors. Structured into seven key chapters (Memory, Violence, Eroticism, Terror, Stereotype, Embarrassment, Resistance), the book explores fundamental aspects of the human experience and its links to the art of theater. The memory chapter discusses the impact of memories on the creative process, emphasizing the importance of using them for authentic performance. Violence is analyzed in terms of its necessity in art, with the role of evoking strong emotional responses. Eroticism is discussed as a driving force in the creative act, while terror is seen as a stimulus for creativity and intensity in the stage event. Stereotypes are reinterpreted as tools for exploring and challenging social perceptions, while embarrassment is presented as a source of artistic vulnerability and authenticity. In the end, resistance is described as a driving force that leads artists to overcome limitations and discover their voices. Anne Bogart's book is not only about directing but also about the psychology and philosophy of theater art, making it essential reading for aspiring and experienced directors alike.